The Reality of Digital Transformation in Jordanian Schools from the Point of view of Teachers - Al-Qatarneh, Marwa Mohammad; Wahba, Fatima AbdAlkareem Khalil (Journal of Educational and Psychological Sciences, 2025)
The study aimed to identify the reality of digital transformation in Jordanian schools from the Point of view of Teachers. The descriptive approach was adopted, and the study tool, a questionnaire, was developed to collect the study data. The validity and reliability of the tool were verified using appropriate methods, and it was distributed to a convenient sample of (400) male and female teachers from public and private Jordanian schools in the Al-Qweismeh district. The study results showed that the degree of digital transformation in Jordanian schools from the teachers' perspective was moderate. The results also indicated that teachers' attitudes towards digital transformation were positive and high. Furthermore, the results revealed that the obstacles to digital transformation in Jordanian schools, from the teachers' perspective, were rated as high. Accordingly, the study recommends several suggestions, most notably: developing internet networks in all schools to ensure high-speed connectivity, providing sufficient devices and software for students and teachers to guarantee equitable access to technology, and organizing workshops and training courses aimed at improving teachers' skills in using digital technology effectively to enhance digital transformation.
Keywords: Attitudes; Obstacles; Digital Transformation; Reality